PENERAPAN ACTIVE CYCLE BREATHING TECHNIQUE (ACBT) TERHADAP BERSIHAN JALAN NAFAS PADA PASIEN TUBERCULOSIS PARU DI RUMAH SAKIT UMUM DAERAH JATISARI - Sumitro Sumitro; Yanti Rosmiyanti; Desty Lismayanti; Sarini Sarini; Okti Rahayu Asih; Cindy Desrianti (Bajang Institute, 2025)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by infection with the bacterium Mycobacteria tuberculosis (M.TB) which attacks the lung tissue and results in impaired ventilation and increased secretion production due to chronic inflammatory processes. Patients with Pulmonary TB often experience in the respiratory tract, this disorder can inhibit daily activities and even have the potential to be life-threatening if not treated appropriately. One non-pharmacological approach that can help improve ineffective road clearance in pulmonary TB patients is the Active Cycle of Breathing Technique (ACBT). This study aims to determine the effect of the application of Active Cycle of Breathing Technique (ACBT) therapy on airway cleaning. The research method used a descriptive design with a case study approach on two patients with pulmonary TB with ineffective airway clearance nursing problems. . Data collection was carried out through interviews, observations, physical examinations, respiratory measurements, oxygen saturation and additional breathing sounds before and after the intervention. The intervention was carried out 3 times a day in 3 days with a duration of 15-20 minutes. The results of this study showed clinical improvements, including a decrease in breathing frequency and an increase in oxygen saturation as well as an improvement in the auscultation of the sound of breath, from heavy ronkhi to ringa ronkhi. The results of these findings show that the application of Active Cycle of Breathing Technique (ACBT) therapy has been proven to be effective in overcoming airway clearance problems in pulmonary TB patients